A interpretação das metáforas através de uma concepção semântico-pragmática: análise da concepção de Searle e da teoria cognitivista de Lakoff - Moreira, Jorge Henrique Lima (2025)
The thesis presented aims to demonstrate a conception of metaphorical interpretation that resolves the difficulties faced by John Searle in his theory of speech acts. The theory of speech acts is the basis for the construction of the thesis, since it is considered that every linguistic utterance is, first and foremost, a speech act. This means that the primacy of the meaning of utterances is to delineate the illocutionary force that determines them. In the meantime, it can be said that metaphor is a speech act. However, Searle fails to present a theory of the metaphors interpretation, since he places the explanation under the incumbency of an indeterminate structure, which does not explain the interpretative procedures. George Lakoff's cognitivist theory considers metaphor as something structural and everyday, so that it considers that metaphors are, for the most part, conventional. The basis of the theory is the idea of metaphorical conceptual mappings, which the author considers as semantic elements. It will be presented as an alternative to the Searlean model, but, in the same way, it will be shown to be an insufficient theory. The solution that the thesis proposes is a theory of semantic-pragmatic interpretation, which contests the two theories mentioned, although it values elements of the analysis of both theories.